Faktor yang Mempengaruhi Motivasi Belajar Santri di Pondok Pesantren Darul Ilmi - Muhammad Efendi; Norhabibi . (Vidya Karya, 2021)
Islamic boarding schools can be used as the best alternative as a place for children in studying education, both in the context of religious guidance and formal general studies. The achievement of quality educational goals and having broad values require high motivation and interest in learning, to realize this, it must be supported by the encouragement of both parents which is applied in the learning environment and family environment. This study aimed to analyze learning motivation and the factors that influence it, which was carried out at Darul Ilmi Islamic Boarding School with a quantitative descriptive approach and random sampling. Based on the data analysis  obtained, there were several factors that influence the motivation of students in learning, as described below: a) 58.6% of students stated that they were motivated by choosing Islamic boarding schools as a place for learning, b) 44.2% of students were motivated to study in Islamic boarding schools because they had basic religious abilities from previous educational institutions, c) 53.9% of students felt calm and comfortable with the atmosphere of Islamic boarding schools, d) 57% of students felt comfortable in the boarding school environment. Based on the indicators, the factor that had a major influence on students' motivation to learn at the Darul Ilmi Islamic boarding school was the desire and ideals of the student to gain knowledge at the Islamic boarding school.Keywords: Motivation; Islamic Boarding Schools; LearningPondok pesantren dapat dijadikan alternatif terbaik sebagai wadah untuk menempatkan anak dalam menimba ilmu pendidikan, baik dalam konteks tuntunan agama maupun kajian umum yang bersifat formal. Ketercapaian tujuan pendidikan yang bermutu dan memiliki nilai yang luas diperlukan motivasi dan minat yang tinggi dalam belajar, untuk mewujudkan hal demikian harus didukung dengan dorongan kedua orang tua yang diterapkan di lingkungan pembelajaran maupun lingkungan keluarga. Penelitian ini bertujuan untuk menganalisis motivasi belajar dan faktor-faktor yang mempengaruhinya, yang dilakukan di Pondok Pesantren Darul Ilmi dengan pendekatan deskriprif kuantitatif dan pengambilan sampel dilakukan secara acak (random sampling). Berdasarkan analisis data yang diperoleh terdapat beberapa faktor yang mempengaruhi motivasi santri dalam belajar, sebagai mana diuraikan berikut ini: a) 58,6% santri menyatakan termotivasi dengan memilih pondok pesantren sebagai wadah untuk belajar, b) 44,2% santri termotivasi untuk belajar di pondok pesantren karena memiliki kemampuan dasar keagamaan dari lembaga pendidikan terdahulu, c) 53,9 % santri merasa tenang dan nyaman dengan suasana pondok pesantren, d) 57% santri merasa nyaman berada di lingkungan pondok pesantren. Berdasarkan indikator di atas terdapat faktor yang memiliki pengaruh besar terhadap motivasi belajar santri di pondok pesantren Darul Ilmi adalah keinginan dan cita-cita santri untuk menimba ilmu di pondok pesantren.Kata Kunci: Motivasi, Belajar, Pondok Pesantren